PENGUATAN PERAN AYAH DALAM PENCEGAHAN COVID-19 DI LINGKUNGAN KELUARGA - Rijal Assidiq Mulyana; Syifa Siti Fatimah (Edueksos: Jurnal Pendidikan Sosial & Ekonomi, 2021)
ABSTRACTThe increasing number of positive cases of Covid-19 has an impact on many things, one of which is the future of children. Children are invisible victims. Thousands of Indonesian children have lost their families to this virus. This reminds us of the importance of Covid-19 prevention measures in the family environment, so that family members have awareness and apply clean and healthy living behaviors. So it requires the direct involvement of a father, as the head of the family. The method used in this study is the library method, which refers to various literature related to strengthening the role of fathers in preventing Covid-19 in the family environment. The results of this study indicate that fathers have an important role in preventing the spread of Covid-19 in the family environment, by strengthening the loving, coaching, and modeling role of a fatherKeywords: Fathers Role, Family Environment